Solve the following equation.
3(t - 3) = 5(2t + 1)
Answers
Answered by
7
Step-by-step explanation:
bracket open then
3t-9=10t+5
-9-5=10t-3t
-14=7t
t=-2
Answered by
50
L. H. S = R. H. S
Hence, it is proved that your answer is correct.
And for more information refer to the attached picture.
#Be_Brainly
Attachments:
![](https://hi-static.z-dn.net/files/d0e/6130e8a8e5a84e9d3b45bad81fa617be.jpg)
Similar questions
Math,
7 months ago
English,
7 months ago
Hindi,
1 year ago
Psychology,
1 year ago
Physics,
1 year ago